1996
DOI: 10.2105/ajph.86.3.324
|View full text |Cite
|
Sign up to set email alerts
|

Long-term psychosocial work environment and cardiovascular mortality among Swedish men.

Abstract: OBJECTIVES. This study examined the effect of cumulative exposure to work organization--psychological demands, work control, and social support on prospectively measured cardiovascular disease mortality risk. METHODS. The source population was a national sample of 12517 subjects selected from the Swedish male population by Statistics Sweden in annual surveys between 1977 and 1981. Over a 14-year follow-up period, 521 deaths from cardiovascular disease were identified. A nested case-control design was used. Wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
200
1
9

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(221 citation statements)
references
References 43 publications
11
200
1
9
Order By: Relevance
“…Johnson et al (1996) suggested that low control over the work process is the true toxic (Light, 1997;Lundberg, 1998) (Kluft & Lansink , 1997;Siegbahn & Ruusuvaara, 1988). The association of BMI with the IRS variables is in agreement with previous findings (Brindley & Rolland, 1989;Reaven, 1988Reaven, , 1996 …”
Section: Discussionmentioning
confidence: 99%
“…Johnson et al (1996) suggested that low control over the work process is the true toxic (Light, 1997;Lundberg, 1998) (Kluft & Lansink , 1997;Siegbahn & Ruusuvaara, 1988). The association of BMI with the IRS variables is in agreement with previous findings (Brindley & Rolland, 1989;Reaven, 1988Reaven, , 1996 …”
Section: Discussionmentioning
confidence: 99%
“…148 Also, low job control, per se, predicts future cardiac events. 149 Taken together, the studies regarding presence of stress at work and subsequent CAD development have been largely positive, suggesting a strong causal relationship between this form of chronic stress and development of atherosclerosis. Because many observational studies have reported psychological prodromata in the months preceding development of acute MI, 150 interest has also been focused on the potential pathogenicity of "subacute" life stress (defined as an accumulation of stressful life events over a duration of months).…”
Section: Chronic and Subacute Life Stressmentioning
confidence: 99%
“…Schnall et al 17 found that diastolic pressure at work was elevated among men with jobs characterised by high demand and low control, and this ®nding has been replicated by others. 18,19 Epidemiological studies of work stress and cardiovascular disease have increasingly focused on low control at work as the toxic element, 20 and low control over the work environment was found in the Whitehall II prospective epidemiological cohort of British civil servants to predict cardiovascular disease independently of standard risk factors. 21 It has also been hypothesised that connections exist between the development of abdominal obesity and psychological stress.…”
Section: Introductionmentioning
confidence: 99%